A CONCISE APPROACH TO FUNCTIONALIZED, HOMOCHIRAL PYRROLIDINONES - Bamford, M; Beard, M; Cherry, D; Moloney, M (1995)
Acylation of O,N-acetal 1 gives excellent yields of the C-7 substituted products 2a,b. Alkylation of 2a under mild conditions gives high yields of the exo- 3 and endo- 4 substituted products in varying ratios, depending on the alkylating agent. The unsaturated derivative 8 reacts in high yields under mild conditions with dienes and 1,3-dipoles to give the corresponding cycloadducts. Elaboration of these compounds by acidic deprotection to substituted pyroglutaminols, and oxidation to the corresponding pyroglutamates, can be readily achieved. © 1995.